THE EFFECT OF SMALL SIDE GAMES AND VO2 MAX EXERCISES ON SOCCER PLAY SKILLS - Raden Dadan Pra Rudiana, - (2018)
The purpose of this study are: (1) To find out overall there are differences in the effect between forms of training small random and blocked side games on mastering the skills of playing football (2) To find out the interaction between the forms of small random and blocked side games training in terms of VO2max on mastery of football playing skills, (3) To find out which form of exercise is better between small random and blocked games at high VO2max level to mastery of playing skills football, (4) To find out which form of training is better between small and random games blocked at low VO2max levels to mastering the skills of playing football. The sample of this study were students who participated in the Football UKM at the University of Subang while the sample technique used a total sampling of 20 samples. The research method used is an experimental method with 2 x 2 factorial design. Based on the results of data processing using SPSS version 16 are as follows (1) There are differences in the effect between the form of training small random and blocked side games on mastery of football playing skills of Fh = 13.11> Ft = 2.71 (2) There is interaction between forms small side games with VO2 Max exercises for Fh = 58.93> Ft = 2.71 (3) There are differences in the effect between the form of training small random and blocked side games on mastery of football playing skills in samples that have a high VO2 Max of Qh = 15 , 4> Qt = 2.95 (4) There is a difference in the effect between the form of training small random and blocked side games on mastering the skills of playing football in a sample that has a Low VO2 Max. equal to Qh = 8.11> Qt = 2.95. The conclusion of the results of this study is that there are differences in the effect of training forms between small side games and VO2 Max on mastering the skills of playing football. ;---Tujuan dari penelitian ini adalah: (1) Untuk mengetahui secara keseluruhan terdapat perbedaan pengaruh antara bentuk latihan small side games random dan blocked terhadap penguasaan keterampilan bermain sepakbola (2) Untuk mengetahui interaksi antara bentuk latihan small side games random dan blocked ditinjau dari VO2max terhadap penguasaan keterampilan bermain sepakbola, (3) Untuk mengetahui manakah bentuk latihan yang lebih baik antara small side games random dan blocked pada tingkat VO2max tinggi terhadap penguasaan keterampilan bermain sepakbola, (4) Untuk mengetahui manakah bentuk latihan yang lebih baik antara small side games random dan blocked pada tingkat VO2max rendah terhadap penguasaan keterampilan bermain sepakbola Sampel penelitian ini adalah mahasiswa yang mengikuti UKM Sepakbola di Universitas Subang adapun teknik sampel menggunakan total sampling sejumlah 20 sampel. Metode penelitian yang digunakan adalah metode eksperimen dengan desain 2 x 2 faktorial. Berdasarkan hasil pengolahan data menggunakan SPSS versi 16 adalah sebagai berikut (1) Terdapat perbedaan pengaruh antara bentuk latihan small side games random dan blocked terhadap penguasaan keterampilan bermain sepakbola sebesar Fh = 13,11 > Ft = 2,71 (2) Terdapat interaksi antara bentuk latihan small side games dengan VO2 Max sebesar Fh = 58,93 > Ft = 2,71 (3) Terdapat perbedaan pengaruh antara bentuk latihan small side games random dan blocked terhadap penguasaan keterampilan bermain sepakbola pada sampel yang memiliki VO2 Max tinggi sebesar Qh = 15,4 > Qt = 2,95 (4) Terdapat perbedaan pengaruh antara bentuk latihan small side games random dan blocked terhadap penguasaan keterampilan bermain sepakbola pada sampel yang memiliki VO2 Max Rendah. sebesar Qh = 8,11 > Qt = 2,95. Kesimpulan hasil penelitian ini adalah terdapat perbedaan pengaruh bentuk latihan antara small side games dan VO2 Max terhadap penguasaan keterampilan bermain sepakbola.